Analisis Penggunaan Analisis Penggunaan Media Pembelajaran Aplikasi Canva Pada Mata Pelajaran Bahasa Arab Di Salafiyyah Ula Tahfizh Ummul Quro - Natasya Abida Syafira; Angga Frananda (Journal of Practice Learning and Educational Development, 2026)
The development of digital technology in the 21st century has had a significant impact on education, including Arabic language learning, which requires innovation in learning media to make the learning process more effective and engaging. This study aims to analyze the use of the Canva application as a learning medium in Arabic language instruction at Salafiyyah Ula Tahfizh Ummul Quro. This research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The informants consisted of an Arabic language teacher, sixth-grade students, the principal, and the vice principal of curriculum. Data were analyzed using the Miles and Huberman model. The findings show that Canva is utilized to visualize learning materials, enhance classroom interactivity, and create flexible and efficient learning media. Canva is also supported by several factors, such as easy access, a wide variety of templates, an auto-save feature, and free templates. However, there are also obstacles, including dependence on stable internet connectivity and longer video downloading processes. In conclusion, the use of Canva contributes positively to improving the quality of Arabic language learning, although adequate technological infrastructure is still needed to optimize its use.